2016
DOI: 10.2147/rrn.s99991
|View full text |Cite
|
Sign up to set email alerts
|

Fetal alcohol exposure and development of the integument

Abstract: Background:The physiology of fetal alcohol exposure changes across gestation. Early in pregnancy placental, fetal, and amniotic fluid concentrations of alcohol exposure are equivalent. Beginning in mid-pregnancy, the maturing fetal epidermis adds keratins which decrease permeability resulting in development of a barrier between fetal circulation and the amniotic fluid. Barrier function development is essential for viability in late pregnancy and in the extra-uterine environment. In this paper we provide a sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Moreover, part of the alcohol excreted via the fetal urine into the amniotic fluid is swallowed back, thus recirculating it into the system, and a small volume of amniotic fluid alcohol is absorbed into fetal compartments via a transmembranous route. These factors make fetus specifically more vulnerable to the adverse effects of maternal alcohol consumption [52].…”
Section: Alcoholmentioning
confidence: 99%
“…Moreover, part of the alcohol excreted via the fetal urine into the amniotic fluid is swallowed back, thus recirculating it into the system, and a small volume of amniotic fluid alcohol is absorbed into fetal compartments via a transmembranous route. These factors make fetus specifically more vulnerable to the adverse effects of maternal alcohol consumption [52].…”
Section: Alcoholmentioning
confidence: 99%
“…As a result, the burden of alcohol use during pregnancy in some African countries is high (3,6,7) . Some authors identified alcohol consumption as a public health problem due to its wide use and the associated fetal and childhood complications (8) , as well as problems related to compromised placental blood flow to the fetus (9) . Furthermore, alcohol acts on the brain in different ways, depending on the type of brain cell and embryo-fetal development stage, leading to structural and functional changes, including cell death and impaired new cell formation (9,10) .…”
Section: Introductionmentioning
confidence: 99%